(untitled) (Biological Sciences - PJSIR, 2022)
Table 2. The confirmation of these methylated fatty acids was carried out by the comparison of mass spectra of unknown compounds with those ofNBS mass spectra library [14]. The relative retention time (RR1) and relative percentages of occurrence of their methylated fatty acids are also shown in Table 2.